Palladium-catalyzed stereo-selective three-component cis-1, 2-arylalkynylation of bicyclic alkenes with aryltriflates and terminal alkynes. (11th May 2022) - Xu, Tianhao; Zhou, Xiangbing; Han, Yuhui; Zhang, Liangwei; Liu, Long; Huang, Tianzeng; Li, Chunya; Tang, Zhi; Wan, Shungang; Chen, Tieqiao
Graphical abstract: Abstract: A palladium-catalyzed stereo-selective cis -1, 2-arylalkynylation of bicyclic alkenes with aryl triflates and terminal alkynes was developed. This reaction showed high functional group tolerance and can be applied to the modification of bioactive molecules. This three-component reaction provided a practical method for preparing the value-added bicyclo[2.2.1]heptanes derivatives.